Second-law-based performance evaluation of cooling towers and evaporative heat exchangers - QURESHI, BILAL AHMED (2020)
Abstract In this paper, we present thermodynamic analysis of counter flow wet cooling towers and evaporative heat exchangers using both the first and second laws of thermodynamics. A parametric study is carried out to determine the variation of second-law efficiency as well as exergy destruction as a function of various input parameters such as inlet wet bulb temperature. Irreversible losses are determined by applying an exergy balance on each of the systems investigated. In this regard, an engineering equation solver (EES) program, with built-in functions for most thermodynamic and transport properties, is used. The concept of total exergy as the sum of thermomechanical and chemical parts is employed in calculating the flow exergies for air and water vapor mixtures. For the different input variables investigated, efficiencies were, almost always, seen to increase or decrease monotonically. We notice that an increase in the inlet wet bulb temperature invariably increases the second-law efficiency of all the heat exchangers. Also, it is shown that Bejan’s definition of second-law efficiency is not limited in evaluating performance. Furthermore, it is understood that the variation in the dead state does not significantly affect the overall efficiency of the system. © 2006 Elsevier Masson SAS. All rights reserved. Keywords: Exergy; Evaporative cooler; Evaporative condenser; Dead state